The City of the Future Living Lab - Sauro Vicini; Sara Bellini; Alberto Sanna (International Journal of Automation and Smart Technology, 2012)
Living lab environments are known to establish and foster innovation, whilst supporting the transition from fundamental to applied research. San Raffaele Scientific Institute’s City of the Future Living Lab in Milan has been created to observe an extended number of users interacting with a great number of services within a real city environment, as well as to engage them in a co-creation process that triggers and helps flourish tomorrow’s e-Services.